Analysis of Transient Behaviour in a Porous Medium Filled Square Cavity Using COMSOL - MUSTAPA, KAMARUZAMAN; KAMARDAN, MUHAMAD GHAZALI (Enhanced Knowledge in Sciences and Technology, 2025)
This study investigates the transient behavior of free convection within a square cavity filled with a porous medium, utilizing the COMSOL Multiphysics software. The dimensionless equations for continuity, Darcy, and energy were solved by producing streamlines and isotherms. The analysis was conducted using Rayleigh numbers (Ra). The focus lies on examining how varying Rayleigh numbers influence heat transfer and fluid flow. The study solves by simulating a system where one vertical wall is heated, the opposite wall is cooled, and the horizontal walls are insulated. These findings underscore the efficacy of COMSOL in modeling complex thermal phenomena and contribute insights relevant to engineering applications, including cooling systems and thermal energy management.